What determines Enterprise Performance in Russia? A Survey of the Evidence - Luc Moers (Tinbergen Institute, 1999)
To achieve sustainable economic growth in the transition countries,it is crucial that enterprise performance is improved. However, it isnot clear which factors are essential for this. On the basis of theempirical literature on potential determinants of enterpriseperformance in Russia, surveyed in this paper, only two firmconclusions can be made. Firstly, more regional competition isrelated with better performance. Secondly, privatization per se isnot. If there is one ownership category performing better, it is newprivate enterprises. The actual situation in Russia on these countsis bad. There is ample room for further empirical research on theabove.
Keywords: D21; P21; P27; P31; 330; Transition economics; Russia; enterprise performance; policy reform; Unternehmenserfolg; Russland